Investigating the cost of offsite construction housing in Western Australia - Sutrisna, M.; Cooper-Cooke, Barry; Goulding, J.; Ezcan, V. (2019)
Purpose: Offsite construction approaches and methodologies have been proffered a potential solution for controlling “traditional” projects, especially where high levels of complexity and uncertainty exist. Given this, locations such as Western Australia (WA), where there are unique housing provision challenges, offsite construction method was considered a potential solution for not only addressing the complexity/uncertainty challenges but also alleviating the housing shortage. However, whilst acknowledging the benefits of offsite construction, recognition was also noted on perceived barriers to its implementation, primarily relating to cost uncertainty. This recognition is exacerbated by very limited offsite construction cost data and information available in the public domain. In response to this, this paper sims to provide detailed cost analysis of three offsite construction projects in WA. Design/methodology/approach: To hold parameters constant and facilitate cross-case comparative analysis, data were collected from three embedded case studies from three residential housing projects in WA. These projects represent the most contemporary implementation of offsite in WA; where two were completed in 2016/2017 and the third project was still ongoing during the data collection of this research. The research methodological approach and accompanying data analysis component engaged a variety of techniques, which was supported by archival study of project data and evidence gathered from the offsite construction provider. Findings: Core findings revealed three emerging themes from residential offsite construction projects pertinent to cost. Specifically, the overall cost of delivering residential housing project with offsite construction techniques, the cost variability of offsite construction residential housing projects as impacted by uncertainties and the cash flow of residential offsite construction projects based on the payment term. These three major cost drivers are elucidated in this paper. Originality/value: This research presents new cost insights to complement the wider adoption of offsite construction techniques. It presents additional information to address the limited cost data and information of offsite construction projects available in the public domain particularly for residential housing projects (within the bounded context of WA). It also highlights the further stages needed to enhance data validity, cognisant of universal generalisability and repeatability, market maturity and stakeholder supply chains.